Opening paths in women’s heterocirculation, between racism and lesbonationalism: some lesbian-feminists experiences in France - Falquet, Jules (Investigaciones Feministas (Feminist Research), 2019)
This article aims at visibilize and re-read after almost twenty years, some experiences made by racialized as well as white lesbian feminists, from the end of the 90s, against racism in the lesbian feminist movement, and then against the nationalist restrictions of french migration politics –using the concept of homonacionalism that first appeared in 2007 in Puar’s work. It starts from the author’s personal experience, having the author participated as an activist as well as an academic, into different ‘women and lesbians in migration’ initiatives. She presents a reflexive perspective on these experiences, re-situating them in a retrospective analysis of the french political conjoncture. The author’s epistemological stand values the importance of the standpoint. In this sense, she highlights the central role that some racialized and proletarized lesbians played, both in struggle and in the analysis. The article evidenciates a first period, between 1999 and 2004, in which the central struggle is the denunciation of racism inside the lesbian movement, which is formulated by a group of racialized lesbians who strongly advocate, for the first time, for an autonomous organization –i.e. racial non-mixity. Between 2005 y 2010, the struggle transforms towards fighting heterosexism in the migrations politics, that become each time more restrictive, and towards visibilizing lesbians’ migration –trough mixed-race initiatives, that are in part, academic ones. In a third moment, the author turns back to the concept of homonationalism, proposing the concepts of heterocirculation of women and lesbonationalism, in order to describe the present situation as well as the action of the new groups.